2016
DOI: 10.1002/dmrr.2797
|View full text |Cite
|
Sign up to set email alerts
|

The influence of clinical and genetic factors on the development of obesity in children with type 1 diabetes

Abstract: The exact cause of the obesity epidemic remains unknown; however, both environmental and genetic factors are involved. People at risk of developing obesity include children with type 1 diabetes mellitus (T1DM), which in turn increases their cardiovascular disease risk. Here, we discuss the clinical and genetic factors influencing weight in patients with T1DM. In children with T1DM, the presence of obesity depends mainly on sex, metabolic control, and disease duration. However, genetic factors, including the fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 59 publications
1
2
0
Order By: Relevance
“…Higher peripheral insulinaemia than that which is normally secreted by the pancreas of children without diabetes could also promote the disposition of fat 18 . Our finding of a higher BMIz in children with type 1 diabetes compared to the background population, and further increased levels in girls compared to boys is consistent with the findings of other studies, 9,17 and excessive fat storage in the abdomen of girls with type 1 diabetes has been suggested as an explanation for this 16 …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Higher peripheral insulinaemia than that which is normally secreted by the pancreas of children without diabetes could also promote the disposition of fat 18 . Our finding of a higher BMIz in children with type 1 diabetes compared to the background population, and further increased levels in girls compared to boys is consistent with the findings of other studies, 9,17 and excessive fat storage in the abdomen of girls with type 1 diabetes has been suggested as an explanation for this 16 …”
Section: Discussionsupporting
confidence: 92%
“…During the last decade, treatment of children with type 1 diabetes has mainly focused on optimizing HbA 1c levels and avoiding severe hypoglycaemic events, and decreasing trends over time in these measures are evident 14,15 . A simultaneous rise in BMI among children with type 1 diabetes can be related both to the general development of obesity caused by environmental or behavioural factors and to intensified diabetes treatment and management aimed at achieving lower HbA 1c goals while preventing severe hypoglycaemia 16 . Earlier studies on the association between HbA 1c and BMI 9,17,18 have reported conflicting results.…”
Section: Introductionmentioning
confidence: 99%
“…Even then, FTO gene polymorphisms have only a small effect on body weight, compared with clinical factors such as sex and metabolic control, which appear to drive the obese phenotype to a larger extent. 23,24 Unlike genetics, which are the "biological fingerprints" of a unique individual, epigenetics does not alter DNA sequence, but affects gene expression through modifications to DNA and histones. 25 Such disruptions occur in the critical period between in utero development and the early postnatal period, and may ultimately affect susceptibility and pathogenesis of diabetes and obesity.…”
Section: Mechanisms and Factors Related To Weight Gain In Women With Diabetesmentioning
confidence: 99%